Vliv sezónní dynamiky jakostních ukazatelů na výkupní cenu mléka v kontextu situace na trhu (Influence of the Season Progress of the Quality Characteristics on to the Purchase Prices of Milk in Context of the Market Situation) - Kateřina Kovářová; Kateřina Procházková (DETUROPE)
In the context of increasing milk production in European Union and overproduction in the Czech Republic (compared to degree of so called self-sufficiency) and difficulties to market the raw milk (due to the degree of market demand for milk and milk products but also due to the market position of dairy processors) is necessary to adopt measures in order to achieve as high quality parameters as possible together with stability of those parameters. The paper investigates progress of the basic quality characteristics of the fresh cow milk on its purchase price in concrete agriculture enterprise. We focused on the quality characteristic CPM and PSB and fat and protein content from 2006 to 2011.The linear and quadratic functions were used for study of the development progress of the quality characteristics. The milk purchase prices are slightly adjusted in purchase contract. The milk purchase price could be scaled in the purchase contract by the sanctions and benefits that depend on the quality characteristics. The average purchase prices of the milk were varied from 6.41 to 8.45 CZK per litter in the Czech Republic. Thanks to the high milk quality the investigated agriculture enterprise reached better prices besides 2009. The worse quality in 2009 was negatively reflected in takings and global economic situation of the enterprise. The long-term monitoring of these characteristics is necessary for investigation of the long-term trends of caring of the production herd and they are also war for reaching of the best purchase prices for this commodity.